Children vaccination of COVID-19 - Sadia Choudhury Shimmi; M. Tanveer Hossain Parash (Penerbit UMS, 2021)
The Delta variant is currently the highly contagious predominant variant of the SARS-CoV-2 virus worldwide that causes severe illness more than the previous variants in unvaccinated people (CDC, 2021). At a White House briefing, the National Institute of Allergy and Infectious Diseases director, Anthony Fauci, predicted that there would be an increase in the number of child hospitalisation proportionate to the increased number of children getting infected with the Delta variant (Press briefing White House, 2021). In response to this situation, the FDA (U.S. Food and Drug Administration) approved Pfizer-BioNTech and Moderna vaccines for children aged 12 – 17 years. Vaccines in children aged 5 – 11 years are currently under clinical trial (Sick-Samuels & Messina, 2021).